The clinical diversity of Lyme disease – diagnostic and therapeutic challenges - Matera, Weronika; Kalinowska, Zuzanna; Aleksandrowicz, Hanna; Krężel, Olga (Journal of Education, Health and Sport, 2025)
Lyme disease is the most common tick-borne disease in Europe, including Poland, where it is endemic and poses a growing public health issue. Caused by Borrelia burgdorferi sensu lato, it is characterized by a wide variety of clinical presentations, which makes it difficult to diagnose correctly. The aim of this study was to analyze the available scientific data on the classic course of Lyme disease and its atypical and asymptomatic forms, as well as to draw clinicians' attention to the diagnostic complexity of this disease. A systematic review of the literature was conducted using PubMed, Google Scholar, and Web of Science databases, covering publications in Polish and English. The results of the analysis indicate that Lyme disease can manifest itself in many forms, ranging from typical erythema migrans, through arthritis and neuroborreliosis, to rare skin and cardiac forms. Asymptomatic cases, which may affect up to 7% of infected individuals, pose a particular challenge. In this group of patients, specific antibodies are present in the absence of clinical symptoms of the disease, and current guidelines do not clearly define the principles of therapeutic management. The lack of characteristic symptoms, limitations of serological tests, and complex clinical course contribute to both delayed diagnosis and overdiagnosis of the disease. The results of the review indicate a need for further research on standardizing diagnostics and developing clear criteria for treating patients with asymptomatic Lyme disease.